(untitled) (Current Horticulture, 2024)
An experiment was conducted to study the pattern of physical changes at 15 days interval after fruit setting till maturity in ber (Zizyphus mauritiana Lamk.) fruits of cv. Narendra Ber Selection-2 during 2019-20 at college of Horticulture and Forestry, Kumarganj, Ayodhya, Uttar Pradesh. The fruits on tagged current season shoots were harvested 21, 36, 51, 66, 81, 96, 111, 126, 141, 156, 171 and 186 days after fruit setting. Samples were collected from main experiment station. The fruit length increased from 0.38 to 3.75 cm and fruit breadth from 0.23 to 3.32cm during 186 days of fruit growth and development. Increase in weight was observed during all stages and maximum weight was 21.02g at harvesting stage.